2014
DOI: 10.1016/j.watres.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of wastewater and activated sludge organics in anaerobic digestion

Abstract: The investigation provides experimental evidence that the unbiodegradable particulate organics fractions of primary sludge and waste activated sludge calculated from activated sludge models remain essentially unbiodegradable in anaerobic digestion. This was tested by feeding the waste activated sludge (WAS) from three different laboratory activated sludge (AS) systems to three separate anaerobic digesters (AD). Two of the AS systems were Modified Ludzack - Ettinger (MLE) nitrification-denitrification (ND) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 13 publications
1
32
2
1
Order By: Relevance
“…The biodegradable fraction of the sludge was estimated 3 times over the duration of the study as per eq 1 and found to range from 0.59 to 0.62 mg COD mg TCOD -1 . The average biodegradable fraction (0.61) was found to be lower than that reported for primary sludge (Ikumi et al, 2014;Parkin and Owen, 1986), while it was higher than the typical values reported for waste activated sludge (Parker, 2005). This was attributed to the use of a mixed primary sludge and WAS in the experiments.…”
Section: Resultscontrasting
confidence: 62%
“…The biodegradable fraction of the sludge was estimated 3 times over the duration of the study as per eq 1 and found to range from 0.59 to 0.62 mg COD mg TCOD -1 . The average biodegradable fraction (0.61) was found to be lower than that reported for primary sludge (Ikumi et al, 2014;Parkin and Owen, 1986), while it was higher than the typical values reported for waste activated sludge (Parker, 2005). This was attributed to the use of a mixed primary sludge and WAS in the experiments.…”
Section: Resultscontrasting
confidence: 62%
“…However, there is evidence (Wentzel et al, 2006, Ikumi et al, 2014 that f up in an anaerobic environment is not very different from f up in an aerobic environment, where it is about f up = 0.08 (Marais and Ekama, 1976) for raw sewage. In that case an estimated value for the apparent yield factor can be calculated: Y ap = 0.05 mgSVS/mgCOD.…”
Section: Resultsmentioning
confidence: 99%
“…However, differences in sewage composition cannot be described by COD. Currently, the Activated Sludge Models (ASMs) as suggested by the International Water Association are the most widely recognized methods for characterizing COD components (Ikumi et al, 2014;Wichern et al, 2006;Wu et al, 2016). The quantitative characterization of these components is required for the application of ASMs.…”
Section: Introductionmentioning
confidence: 99%